Simultaneous relationship among market performance, risk and disclosure quality: empirical evidence from Malaysian listed banks - Htay, Sheila Nu Nu; Salman, Syed Ahmed; Sufian, Fadzlan (Contemporary Research Center Australia, 2013)
Without doubt, higher performance is the ultimate objective of any business entity while minimizing the risk and informing the investors the transparent information of the business. In this paper we show a new way of thinking that willfulfill the ultimate interests of the banks due to the efforts of management such as being higher market value of the firms, taking less risk and providing higher level of disclosure for the stakeholders in general and the shareholders, in particular. We use simultaneous relationship among market performance, risk and disclosure quality of twelve Malaysian listed banks over a period of ten years from 1996 until 2005. Tobin’Q, standard deviation of monthly stock return and weighted disclosure score are analyzed. Three theories, namely, signaling theory, risk and return theory and market discipline theory are tested and only market discipline theory is found to be significant indicating that banks are highly regulated compared to other industries, especially in terms of risk factors and information disclosure.